EROMM and the Registry of Digital Masters - Schwartz, Werner (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
Since the invention of printing the spread of ideas and knowledge has been in the mind of authors when publishing their work in the new medium. The aim to make a profit from printing and distributing was naturally in the mind of producers and distributors, i.e., printers, publishers and book traders. To achieve this they needed to make their products known as widely as possible. And they used the new medium itself for this purpose.